PENGARUH SUBKULTUR DAN LAMA PERIODE KULTUR PADA DAYA MULTIPLIKASI TUNAS LADA (Piper nigrum L.) ASAL BIJI VARIETAS PETALING I - NATALINI NOVA KRISTINA; NURLIANI BERMAWIE (Jurnal Penelitian Tanaman Industri, 1999)
Effect subculture and culture period on shoot multipli¬ cation in black pepper Petaling IAn expeiment on shoot multiplication in black pepper Petaling I from planting to until shoot multiplication changes and the effect of culture peiod, was conducted in the Laboratory of Genetic Research and Breeding of Balittro. Bogor from May 1997 to June 1998. The seeds wee germinated on MS medium without growth regulator. Ater sprouting the shoots wee removed to MS multiplication medium + BA 0.3 mg/1 + polypynyl pyolidon 200 mg/1 for subcultue and culture peiod. In the subculture expeiment, explant was removed after 3 months to new medium. In the cultue peiod the explant was visible until 4 months after that, explant was removed to new medium. The results showed that the highest multiplication rate was found after 3'° subculture with 9.2 shoots and the best cultue peiod was three months with 9.3 shoots. After 4* months the shoots died, due to fenolic activity which changed pH medium from acidic (5.8 to basic 7.13).